The 3D genome of plasma cells in multiple myeloma - Kaiji Zhang; Mengsi Chen; Ming Chen; Yue Wang; Haibo Liu; Yanju Li; Xiaohong Guan; Lihua Lei; Li Tao; Xiaoxiao Liu; Dong He; Xiaoli Fei (Scientific Reports)
Abstract Multiple myeloma (MM) is a hematological malignancy characterized by expanding clonal plasma cells in the bone marrow (BM) that produce monoclonal immunoglobulin. It is an incurable disease, accounting for about 10% of blood malignancies and the second most common hematologic malignancy. Therefore, in-depth research into the molecular mechanisms and therapeutic targets of the disease is crucial. For the first time, we performed high-throughput chromosome conformation capture (Hi–C) analysis of plasma cells in five multiple myeloma patients, and integrated it with genome resequencing and transcriptomic associated with genomic variation and gene expression. As a result, 19 specific TAD (Topologically Associating Domain) boundaries in MM samples related to the immune response and Wnt signaling pathways were identified. Additionally, Loop structures were also analyzed, revealing that promoter-enhancer-associated loops were the most prevalent. Genomic characteristics of MM patients were explored, identifying SNPs, InDels, and CNVs, with variations in the CDS region potentially affecting gene function. Transcriptome analysis showed differentially expressed genes in MM patients, mainly involved in p53 signaling and cell adhesion. Multi-omics analysis identified overlapping genes related to MM, including those involved in MHC class II protein complex assembly and antigen presentation. The study provides insights into the complex genomic and transcriptomic changes in MM plasma cells, potentially aiding in identifying therapeutic targets.